2017
DOI: 10.7152/jipa.v41i0.15011
|View full text |Cite
|
Sign up to set email alerts
|

Shell Personal Ornaments Craft at the Site of Tha Kae, Lopburi Province, Central Thailand. Tracing the Southward Dispersal of the Drilling Technique

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…We are therefore inclined to conclude that the copper-base artefacts in the Bronze Age phase 2 burials were imported as finished artefacts, with the Khao Wong Prachan Valley being the only source of copper confidently identified at present . This harmonises with the known presence of shell-bangle workshops in the Khao Wong Prachan Valley and vicinity-the most likely origin for the nearly 1000 Tridacna and Trochus shell bangles worn by those interred at Ban Non Wat, along with copper-base tools and ornaments (Ciarla et al 2017).…”
Section: Integrating Production and Consumption: Ban Non Wat As A Cassupporting
confidence: 69%
See 1 more Smart Citation
“…We are therefore inclined to conclude that the copper-base artefacts in the Bronze Age phase 2 burials were imported as finished artefacts, with the Khao Wong Prachan Valley being the only source of copper confidently identified at present . This harmonises with the known presence of shell-bangle workshops in the Khao Wong Prachan Valley and vicinity-the most likely origin for the nearly 1000 Tridacna and Trochus shell bangles worn by those interred at Ban Non Wat, along with copper-base tools and ornaments (Ciarla et al 2017).…”
Section: Integrating Production and Consumption: Ban Non Wat As A Cassupporting
confidence: 69%
“…This harmonises with the known presence of shell-bangle workshops in the Khao Wong Prachan Valley and vicinity—the most likely origin for the nearly 1000 Tridacna and Trochus shell bangles worn by those interred at Ban Non Wat, along with copper-base tools and ornaments (Ciarla et al . 2017).…”
Section: Integrating Production and Consumption: Ban Non Wat As A Casmentioning
confidence: 99%
“…These all contained bangles, bracelets, earrings, necklaces, pendants and miscellaneous loose beads manufactured from shells, soft stones, hard stones, bronze, tin, tiger teeth and shark teeth, which presents some similarities with other archaeological sites like Samrong Sen. Their distribution also suggested that status was acquired rather than ascribed (child burials were less wealthy) (Chang, 1996). Beads are probably the most widely travelled of all prehistoric artefacts (Ciarla, Rispoli, & Yukongdi, 2017; Higham et al, 1992; Ramli, Shuhaimi, & Rahman, 2008). They are thus a good proxy for reconstructing the extent of networks over time (Bellina, 2003; Chang, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Excavations of Ban Mai Chaimongkol conducted by the Silpakorn University Department of Archaeology identified 59 burials, mostly single inhumations (Natapintu, , ), including several individuals with missing teeth attributed to potential ritual dental modification (Chinmalai et al ). Excavations of Tha Kae conducted by the Thai‐Italian Lopburi Regional Archaeological Project (LoRAP) documented 27 graves, many with multiple inhumations (Ciarla, Rispoli, & Yukongdi, ).…”
Section: Methodsmentioning
confidence: 99%